THE ANNULLMENT OF A MARRIAGE DUE TO DEATH IN A POLYGAMOUS SITUATION - Daffanza Azriel Rochadi, (Master of Law Faculty of Law UNISSULA, 2023)
A man and a woman are bound by law and religion when they get married. Under Indonesian positive law, a marriage cannot be formally recognized unless it is registered. However, many marriages-especially polygamous marriages-take place without being officially registered. The legal ramifications of polygamous marriages when one partner passes away are examined in this article. Many polygamous marriages fail for a variety of reasons, according to the literature review that was done, including bureaucratic roadblocks, a lack of awareness regarding the significance of registration, or willful avoidance of registration to evade legal ramifications. But when one of the partners passes away, issues come up, particularly with regard to children from the marriage and inheritance rights. Unregistered marriages are voidable under current law. But the annulment of divorces resulting from death has turned into a contentious issue. This is a result of the bereaved spouse's many struggles to obtain their legal rights, including those related to inheritance and child custody. In order to safeguard the rights of surviving spouses in polygamous marriages, this article suggests changing rules and promoting education about marriage registration.